Vloga predmetnega učitelja v sodobni šoli (University of Maribor Press, 2023)
The Role of Subject Teacher in the Contemporary School.In the last decade, we have witnessed great technological, social and social changes. The differences between individuals in society are increasing and capitalism is slowly but steadily changing human values. Children are the most vulnerable stakeholders of this society, so it is necessary to provide them with quality education. The role of a subject teacher in a modern school is therefore very responsible. It requires regular reflection of one’s own practice and improvement planning. At the same time, it also requires lifelong education and the integration of innovations into the pedagogical process. The contributions in the monograph deal with various aspects of education at the subject level: the safety aspect of teaching chemistry, creativity and its connection with technical education and care for a positive learning climate in biology classes. Current topics are intended for subject teachers of science subjects, mathematics and technology, as well as students who are studying for this profession.